Island Ecology and Early Canadian Women Writers - Campbell, Wanda (Studies in Canadian Literature / Études en littérature canadienne, 2014)
The island, and the fresh water island in particular, is a recurring motif in the work of early Canadian women writers. Using an eco-critical perspective to explore Susan Frances Harrison’s short story “The Idyl of the Island” (1886), Marjorie Pickthall’s short story “On Ile de Paradis” (1906), and Katherine Hale’s long poem, “The Island (Experiment in Magic)” (1934), as well as “island” lyrics by all three authors, we discover tentative but compelling expressions of nature as a place of ambiguous potential and power, depending on the attitude and actions of those who approach it. Focusing as they do on the interaction between human beings and nature, the island texts of early Canadian women writers may be more anthropocentric than biocentric, but they are nonetheless illuminated in the light of three areas of concern in the field of island biogeography: colonization, competition, and trophic cascade. Nature as a virgin to be violated has been a longstanding trope of masculine writing about the wilderness, but Harrison, Pickthall, and Hale point us instead in the direction of nature as mother and sister. In their work, the island conveys an unforgettable message—that it is folly for us to believe we can conquer nature, come to her unprepared, or expect to separate ourselves from her fate.